Waist-to-height ratio and body roundness index as predictors of insulin resistance in Pakistani adults: a gender and age stratified analysis - Mukhtar, Haseeba; Kakakhel, Susan; Obaid, Seher; Alamgir, Alina; Shinwari, Mah Rukh; Shah, Burhan Ali (International Journal of Pathology, 2025)
Background: A major risk factor for metabolic syndrome and type 2 diabetes mellitus (T2DM), insulin resistance (IR) is especially common in South Asian populations. One of the main causes of IR, central adiposity, is not well represented by traditional anthropometric measures such as the body mass index (BMI) and waist-to-hip ratio (WHR). Using gender- and age-stratified analyses, this study examines the diagnostic value of the Waist-to-Height Ratio (WtHR) and Body Roundness Index (BRI) in predicting IR in Pakistani adults. Methods: In this cross-sectional study, 1,592 adults aged 18–70 years were recruited from tertiary care hospitals in Peshawar, Pakistan. IR was defined with a threshold of >2.5 using the Homeostasis Model Assessment of Insulin Resistance (HOMA-IR). WtHR, BRI, BMI, WHR, and Abdominal Volume Index (AVI) were calculated using anthropometric data (height, weight, and waist circumference). Youden Index (J) and Receiver Operating Characteristic (ROC) curves were used to assess diagnostic performance, with subgroup analysis by age (≥60 years vs. ≥60 years) and gender. Results: WtHR showed the highest area under the curve (AUC = 0.710), followed by BRI (AUC = 0.707). The optimal cut-off for WtHR (0.54) achieved 71% sensitivity and 69% specificity (J = 0.40), while BRI (cut-off: 4.2) yielded 69% sensitivity and 68% specificity (J = 0.37). Conclusion: WtHR and BRI are better at predicting insulin resistance than traditional indices, especially in younger and female populations. In resource limited environments, such as Pakistan, their non-invasive nature and ease of use make them useful instruments for early IR screening.